Detección de Polymyxa graminis en trigo en campos de Corrientes y Córdoba - Solis, Valentina Eva; Gómez Montenegro, Brenda Emiliana; Pozzi, Elizabeth Alicia; Luciani, Cecilia Elizabeth; Dumon, Analia Delina; Perotto, Maria Cecilia; Gutiérrez, S.A.; Alemandri, Vanina Maria; Celli, Marcos Giovani (Asociación Argentina de Fitopatólogos (AAF), 2024)
Poster